2018
DOI: 10.1017/s0266467418000202
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and division of the South and South-East Asian flora in relation to tectonics and climate change

Abstract: Abstract:The main phases of plant dispersal into, and out of the South-East Asian region are discussed in relation to plate tectonics and changing climates. The South-East Asian area was a backwater of angiosperm evolution until the collision of the Indian Plate with Asia during the early Cenozoic. The Late Cretaceous remains poorly understood, but the Paleocene topography was mountainous, and the climate was probably seasonally dry, with the result that frost-tolerant conifers were common in upland areas and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
170
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(178 citation statements)
references
References 156 publications
(279 reference statements)
8
170
0
Order By: Relevance
“…In contrast to the scarce record of plant macrofossils, there are a wealth of Cenozoic palynological data and interpretations available from Malesia (Morley 1982(Morley , 1998(Morley , 2002(Morley , 2003(Morley , 2018aLelono & Morley 2011;Witts et al 2012). Palynological data represent extremely high sample sizes and stratigraphic densities, form the basis of biostratigraphic correlations, and provide evidence of numerous lineages not preserved as macrofossils, although isolated palynomorphs often do not provide sufficient information to allow unambiguous phylogenetic placement on a crown versus a stem lineage (Sauquet et al 2009).…”
Section: Paleobotanical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the scarce record of plant macrofossils, there are a wealth of Cenozoic palynological data and interpretations available from Malesia (Morley 1982(Morley , 1998(Morley , 2002(Morley , 2003(Morley , 2018aLelono & Morley 2011;Witts et al 2012). Palynological data represent extremely high sample sizes and stratigraphic densities, form the basis of biostratigraphic correlations, and provide evidence of numerous lineages not preserved as macrofossils, although isolated palynomorphs often do not provide sufficient information to allow unambiguous phylogenetic placement on a crown versus a stem lineage (Sauquet et al 2009).…”
Section: Paleobotanical Backgroundmentioning
confidence: 99%
“…The aseasonal (perhumid) rainforests of Malesia (Figure 1) may rival or exceed the Amazon forests in tree species richness (Slik et al 2015). They have assembled through time from lineages with remarkably different biogeographic histories (van Steenis 1934;Morley 2003Morley , 2018aSlik et al 2018) while providing habitat for a rich diversity of nonwoody plants, as well as terrestrial, arboreal, flying, gliding, and aquatic animals. Many of the region's lowland and other habitats have been cleared for settlement and agriculture on an industrial scale (Ashton 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the centre are the numerous smaller terranes and oceanic islands that comprise the Philippines and Wallacea, and in the east is the Sahul shelf and the large island of New Guinea, which is itself of composite origin. Adding a layer of complexity to this is the changing climate of the past 50 ma (Morley 2012(Morley , 2018, most strikingly the fluctuating glacials and interglacials of the Pleistocene (Woodruff 2010, Morley 2012, which impacted sea levels and the extent of vegetation types (Woodruff 2010, Cannon 2012, Morley 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on phytogeographic aspects have also been undertaken. In an important contribution, Morley (2018) recently discussed the issue of plant dispersal in to and out of India and South-East Asia in relation to plate tectonics and climate change. He suggested that India's drift into the perhumid low latitudes during the Eocene resulted in the dispersal of diverse groups of megathermal angiosperms into South-East Asia.…”
Section: Fossil Floras and Paleoclimatesmentioning
confidence: 99%